Mind the gap: What explains Malaysia’s underperformance in Pisa? - Perera, Liyanage Devangi H.; Asadullah, M. Niaz (Elsevier, 2019)
East Asia's phenomenal economic rise has been attributed to its early investment in human capital. While countries such as South Korea and Singapore dominate in international student assessments, other countries from the region (e.g. Malaysia) lag far behind despite heavy spending in education. This paper assesses student performance in mathematics, science and reading in Malaysia vis-à-vis Korea and Singapore by examining the relative contribution of individual, family background, school, teacher and institutional factors in explaining between-country test score differences. Oaxaca-Blinder decomposition analysis is performed using data from the 2012 round of Programme for International Student Assessment (PISA) to determine how much of the between-country test scores gap can be explained by observed family and school specific characteristics. Our results demonstrate that while socio-economic and school specific factors matter, more than half of the achievement gap between the two high performers and Malaysia remains unexplained even after accounting for the contribution of those factors. We conclude by highlighting policy, institution and culture related explanations for this unexplained gap. © 2018 Elsevier Ltd